Sliver Solar Cells: High-Efficiency, Low-Cost PV Technology. (2nd September 2007) - Franklin, Evan; Everett, Vernie; Blakers, Andrew; Weber, Klaus
Abstract : Sliver cells are thin, single-crystal silicon solar cells fabricated using standard fabrication technology. Sliver modules, composed of several thousand individual Sliver cells, can be efficient, low-cost, bifacial, transparent, flexible, shadow tolerant, and lightweight. Compared with current PV technology, mature Sliver technology will need 10% of the pure silicon and fewer than 5% of the wafer starts per MW of factory output. This paper deals with two distinct challenges related to Sliver cell and Sliver module production: providing a mature and robust Sliver cell fabrication method which produces a high yield of highly efficient Sliver cells, and which is suitable for transfer to industry; and, handling, electrically interconnecting, and encapsulating billions of sliver cells at low cost. Sliver cells with efficiencies of 20% have been fabricated at ANU using a reliable, optimised processing sequence, while low-cost encapsulation methods have been demonstrated using a submodule technique.